Porsi Waris Anak Laki-Laki dan Perempuan Masyarakat Tionghoa : Kajian Putusan Mahkamah Agung Nomor 147 K/Pdt/2017 - Yuni Kamilaini; Muhammad Arifin; Isnina Isnina (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Inheritance law in Indonesia is pluralistic because it is influenced by three legal systems, namely customary law, Islamic law, and western civil law (Burgerlijk Wetboek) which is a legacy of the Dutch colonial era and divides the population based on legal classes. This diversity of legal systems also influences inheritance practices in Chinese society which traditionally adheres to a patrilineal system, where sons are prioritized over daughters in the distribution of inheritance. This study aims to analyze the inheritance law regulations for Chinese society, the development of inheritance practices that occur, and the legal considerations used by judges in the Supreme Court Decision Number 147K/Pdt/2017. The research method used is normative-empirical legal research with a statutory approach, cases, and legal identification, as well as assessing the effectiveness of legal implementation through literature studies and interviews. The results of the study indicate that the Supreme Court decision confirms the equality of inheritance rights between sons and daughters. This marks a shift in the Chinese inheritance system from patrilineal customs to the application of the provisions of the Civil Code, which upholds the values ​​of justice and gender equality.